2022
DOI: 10.1101/2022.03.03.22271862
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burden of Disease from Contaminated Drinking Water in Countries with High Access to Safely Managed Water: A Systematic Review

Abstract: BackgroundThe vast majority of residents of high-income countries (>90%) reportedly have high access to safely managed drinking water, the highest level of service under the Sustainable Development Goal (SDG) framework. Owing perhaps to the widely held perception of near universal access to high-quality water services in these countries, the burden of waterborne disease in these contexts is understudied.MethodsWe conducted a systematic review of estimates of the disease burden attributed to drinking water i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…It has been noted in other studies that a lack of access to safe drinking water in the United States is associated with race/ethnicity, as well as poverty. 49,50 In a study of environmental injustice regarding a population's nearness to unconventional gas development in the state of Pennsylvania, Clough and Bell in 2016 found that race and ethnicity were not associated with proximity to unconventional gas development, but poverty was. 20 With regards to minority race and/or ethnicity, we found that the census tracts with the highest proportions of minority populations were more likely to have access to public water.…”
Section: Race/ Ethnicity and Povertymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted in other studies that a lack of access to safe drinking water in the United States is associated with race/ethnicity, as well as poverty. 49,50 In a study of environmental injustice regarding a population's nearness to unconventional gas development in the state of Pennsylvania, Clough and Bell in 2016 found that race and ethnicity were not associated with proximity to unconventional gas development, but poverty was. 20 With regards to minority race and/or ethnicity, we found that the census tracts with the highest proportions of minority populations were more likely to have access to public water.…”
Section: Race/ Ethnicity and Povertymentioning
confidence: 99%
“…Approximately 90% of the US is considered to have access to safely managed drinking water 17,49 , which in the context of the US is deceiving, as this number includes those served by private, unregulated, untested and untreated domestic wells. If we were to say that only those served by public drinking water in US have access to safely managed drinking water, then this number would be drastically decreased.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…The obvious case in point is the extreme inequities faced in Flint, Michigan among lower-income neighborhoods due to lead exposure (e.g., Campbell et al, 2016). Unfortunately, other examples abound and are more often than not the result of systemic racism and a history of racist policies within societies (Brown et al, 2023;Lee et al, 2023).…”
Section: Genechips™ To Whole Genome Sequencing and Metagenomicsmentioning
confidence: 99%
“…Today, water safety is a particular concern in low-income countries in the Middle East, Northern Africa, Central Asia, and Southern Asia, due to rapidly expanding urban areas, hobbled water infrastructure and distribution systems, and limited resources to address water crises. , Indeed, low-income countries tend to have fewer safeguards against unsafe drinking water, as indicated by Yale’s Environmental Performance Index . However, a recent review highlights that threats to water safety also affect residents of high-income countries in the Global North, especially those who live in rural households that rely on private wells for drinking water. , The United States Environmental Protection Agency (EPA) estimates that 23 million American households rely on private wells, which are prone to contamination. , Even in countries in which at least 90% of the population had access to safely managed water sources, 3,529 per 100,000 people yearly are estimated to develop gastrointestinal illnesses attributable to drinking water …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Even in countries in which at least 90% of the population had access to safely managed water sources, 3,529 per 100,000 people yearly are estimated to develop gastrointestinal illnesses attributable to drinking water. 16 To protect against unsafe drinking water, agencies such as the United States Centers for Disease Control and Prevention (CDC), 17 United Nations Children's Fund (UNICEF), 18 and the EPA 19 bottled water for emergencies and treating potentially contaminated water by boiling or with chemicals (e.g., chlorine, diluted bleach). For well owners, it is also important to regularly monitor and test water quality.…”
Section: ■ Introductionmentioning
confidence: 99%